The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/aoc.1703
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and anti‐microbial studies of cadmium(II) compounds containing 3,10‐C‐meso‐Me8[14]aneC. Crystal and molecular structure of cis‐[CdLC(NO3)](NO3)

Abstract: − ligand is replaced by two monodentate ligands that occupy axial positions. All compounds were characterized on the basis of analytical, spectroscopic, conductometric and magnetochemical data. The crystal structure of cis-CdL C (NO 3 )](NO 3 ) was determined by X-ray crystallography and showed the cadmium centre to exist within a cis-N 4 O 2 donor set that defined a distorted octahedral geometry. Non-systematic variations in the Cd-O and Cd-N bond distances were correlated with significant hydrogen bonding in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
5
3
0
Order By: Relevance
“…The latter value is longer than the sum of ionic radii (Cd 2+ CN7 : 1.03 Å; O 2– : 1.35 Å). Similar values were reported for CdN 4 O 3 in the CTP environment, and as expected, the Cd–O bond to the capping O 2– is longer than to O 2– anions in the trigonal prism. The Cd–N bonds are between 2.196 and 2.485 Å (Table S8), in agreement with literature values. The N–Cd–N and O–Cd–O cis angles range from 74.4(4)° to 97.9(4)°, respectively, from 62.96(14)° to 65.78(14)°, and the N–Cd−μ 2 -O angles are 74.2(3)–96.8(3)°. The trans angles cover a wide range as expected by different orientations of the monocapped trigonal prisms (Table S9), but the geometric parameters are not unusual and similar data were reported in the literature. ,, …”
Section: Resultssupporting
confidence: 89%
“…The latter value is longer than the sum of ionic radii (Cd 2+ CN7 : 1.03 Å; O 2– : 1.35 Å). Similar values were reported for CdN 4 O 3 in the CTP environment, and as expected, the Cd–O bond to the capping O 2– is longer than to O 2– anions in the trigonal prism. The Cd–N bonds are between 2.196 and 2.485 Å (Table S8), in agreement with literature values. The N–Cd–N and O–Cd–O cis angles range from 74.4(4)° to 97.9(4)°, respectively, from 62.96(14)° to 65.78(14)°, and the N–Cd−μ 2 -O angles are 74.2(3)–96.8(3)°. The trans angles cover a wide range as expected by different orientations of the monocapped trigonal prisms (Table S9), but the geometric parameters are not unusual and similar data were reported in the literature. ,, …”
Section: Resultssupporting
confidence: 89%
“…Relevant to the present study are recent reports describing the antibacterial activities of cadmium compounds [11,12,13,14]. These follow earlier studies, whereby cadmium(II) macrocyclic compounds were reported to exhibit potent antibacterial potential [13,14]. In addition, we have also reported x-ray crystallographic studies of cadmium(II) compounds with other macrocycles [14,15].…”
Section: Introductionsupporting
confidence: 82%
“…Due to the multifarious applications [1,2,3,4,5,6,7,8,9,10] of macrocyclic ligands, including differential behavior exhibited by their isomeric forms and their metal complexes in a wide variety of contexts, researchers continue to be fascinated by their chemistry and various applications, including in the development of metal-based drugs and as imaging agents. Relevant to the present study are recent reports describing the antibacterial activities of cadmium compounds [11,12,13,14]. These follow earlier studies, whereby cadmium(II) macrocyclic compounds were reported to exhibit potent antibacterial potential [13,14].…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations